Modeling and performance analysis of IP with MPLS/GMPLS over backbone networks - Shao, Xuguang (2009)
Backbone network is at the core of the computer network infrastructure and we aim to model and analyze the performance of the backbone network under various conditions. In a copper–based or opaque fiber–based backbone network, Integrated Service (IntServ) and Differentiated Service (DiffServ) should be viewed as complementary technologies in the pursuit of end–to–end Quality of Service (QoS). Multi–Protocol Label Switching (MPLS) is a good candidate that facilitates the interoperation of the IntServ and DiffServ network. Meanwhile, with the introduction of Generalized Multi–Protocol Label Switching (GMPLS) as the common control plane between optical crossconnects (OXCs) and electronic switching devices, the integration of Internet Protocol (IP) and Wavelength Division Multiplexing (WDM) can be efficiently achieved. In the case of all–optical IP over WDM network, traffic flows can be directly mapped to optical channels without the intermediate layers such as Asynchronous Transfer Mode (ATM) and Synchronous Optical Networking (SONET) / Synchronous Digital Hierarchy (SDH). Therefore, the bursty nature of IP traffic may have significant effect on the performance of the optical channels. On the other hand, the optical impairments of the optical paths and optical nodes may greatly influence the performance of IP traffic at the network layer. In this thesis, new traffic classification and service mapping among the IntServ, DiffServ and MPLS/GMPLS are proposed to enable the interoperation of these technologies. More importantly, a novel four–queue system is proposed to be located at every output port of the MPLS Label Switch Router (LSR) or GMPLS OXCs, but in different manners respectively. The functionally equivalent electronic queueing system and optical queueing system are illustrated in great details. In this way, the network node in the backbone is able to ensure the QoS of both the IntServ and DiffServ edge customers. The performance analysis of the four–queue system is elaborated and the performance parameters in terms of throughput, loss probability and delay are derived analytically.